Improving the pelvic exam experience: Sheathed vs Conventional Cusco’s Speculum for visualization of the Cervix - Vishwas Gaikwad, Suhas; Ajit Gaikwad, Vidya; Anil Phutane, Rushikesh (Journal of Neonatal Surgery, 2025)
Background: Pelvic examinations are essential in gynaecologic care but are often associated with pain and discomfort, leading to avoidance and delayed diagnoses. Innovations in speculum design and technique could improve patient comfort and examination outcomes. Objectives: To compare pain experienced during pelvic examination using a conventional Cusco’s speculum versus a Cusco’s speculum sheathed with a lubricated condom using the Wong-Baker FACES Pain Rating Scale. To compare the area of cervical visualization between the two methods. Methods: A controlled clinical trial was conducted from October 2022 to September 2025 at the Department of Obstetrics and Gynaecology, Dr. D.Y. Patil Medical College, Pune. A total of 126 consenting participants aged over 18 were randomized into two groups (n=63 each): one underwent pelvic examination using a conventional Cusco’s speculum, and the other with a sheathed Cusco’s speculum using a NIRODH condom. Pain scores, area of cervix visualized, time to cervical visualization, and examiner’s experience (ease of insertion, manipulation, need for repositioning) were recorded and statistically analyzed using SPSS version 26.0. Results: The mean pain score was significantly lower in the sheathed group (2.3 ± 1.4) compared to the conventional group (4.1 ± 1.7) (p<0.001). The mean area of cervical visualization was higher with the sheathed speculum (95.1% ± 4.3) than with the conventional speculum (76.4% ± 8.6) (p<0.001). Cervix visualization time was shorter in the sheathed group (29.8 ± 9.4 seconds) than the conventional group (47.6 ± 13.2 seconds) (p<0.001). Examiner-rated ease of use and manipulation were also significantly better with the sheathed speculum. Repositioning was required in only 9.5% of cases in the sheathed group versus 30.2% in the conventional group (p=0.004). Patient preference was higher for the sheathed speculum, with 67.5% favouring it for future exams. Conclusion: The sheathed Cusco’s speculum significantly improves patient comfort, provides better cervical visualization, reduces examination time, and is preferred by both examiners and patients. It presents a simple, cost-effective alternative to improve pelvic examination experience in outpatient gynecological settings